MCTS1 as a Novel Prognostic Biomarker and Its Correlation With Immune Infiltrates in Breast Cancer - Deng, Mei; Xiong, Chao; He, Zhuo-Kai; Bin, Qiong; Song, Jing-Zhi; Li, Wei; Qin, Jie (Frontiers in Genetics, 2022)
Multiple copies in T‐cell lymphoma‐1 (MCTS1) plays an important role in various cancers; however, its effects on patient prognosis and immune infiltration in breast cancer remain unclear. In this study, the expression profiles and clinical information of patients with breast cancer were obtained from the Cancer Genome Atlas (TCGA) database. Using the Wilcoxon rank-sum test, the MCTS1 expression levels were compared between breast cancer and normal breast tissues. Functional enrichment analyses were performed to explore the potential signaling pathways and biological functions that are involved. Immune cell infiltration was assessed using single-sample gene set enrichment analysis. The UALCAN and MethSurv databases were used to analyze the methylation status of the MCTS1. The Kaplan–Meier method and Cox regression were used to identify the prognostic value of MCTS1. A nomogram was constructed to predict the overall survival (OS) rates at one-, three-, and five- years post-cancer diagnosis. MCTS1 was overexpressed in breast cancer and significantly associated with the M pathological stage, histological type, PAM50, and increased age . MCTS1 overexpression contributes to a significant decline in OS and disease-specific survival. Multivariate Cox analysis identified MCTS1 as an independent negative prognostic marker of OS. The OS nomogram was generated with a concordance index of 0.715. Similarly, the hypomethylation status of MCTS1 is also associated with poor prognosis. Functional enrichment analysis indicated that the enriched pathways included the reactive oxygen species signaling pathway, MYC targets, interferon alpha response, immune response regulating signaling pathway, and leukocyte migration. Moreover, the overexpression of MCTS1 was negatively correlated with the levels of immune cell infiltration of natural killer cells, CD8+ T cells, effector memory T cells, and plasmacytoid dendritic cells. Therefore, MCTS1 maybe a novel prognostic biomarker.